(untitled) (Fiep Bulletin - online, 2012)
This work is a documentary research that seeks to approach the ballet in the periodicals catalog of the Physical Education developed by Proteoria group. It aims to identify and analyze through Periodicals Catalog of Physical Education and Sport (1930-2000) the articles on the subject under investigation. The consistent basis of this study was Periodicals Catalog of Physical Education and Sport, being researched articles in 36 journals of Physical Education of the period from 1930 to 2000, using key words ballet, ballet dancer and dancer in the titles of periodicals. We found 13 articles on ballet presented in 07 journals, most of the articles published in 1999. In view of the data analysis, the study demonstrates the need to expand the production of the ballet, it is noted a lack of production in this context, suggesting new studies on the subject under investigation.